Differences in Thyroid Function and Autoantibodies in the Development of Guillain–Barré Syndrome vs. Chronic Inflammatory Demyelinating Polyradiculoneuropathy - Tu, Yu; Gong, Xuan; Zeng, Guanwen; Zhuo, Wenyan; Li, Zhaoxia; Yu, Xueying (Frontiers in Neurology, 2020)
Background Both Guillain–Barré syndrome (GBS) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) are neurodegenerative and inflammatory demyelination disorders. Sporadic reports showed that the increased levels of thyroid function and autoantibodies are associated with GBS, CIDP or both, but no systematic study has been reported. We assessed the differences of thyroid function and autoantibodies between GBS and CIDP in a Chinese cohort. Methods A total of 256 patients were enrolled in this study. 175 clinically confirmed GBS and CIDP patients were selected. Meanwhile, 81 patients hospitalized for diseases other than GBS or CIDP with mild symptoms were enrolled as a control group. Relevant clinical data, including thyroid function and autoantibody examinations, were collected for statistical analysis. Results In the comparison of thyroid function and autoantibody parameters, the levels of total thyroxine (TT4), thyroid peroxidase antibody (TPO-Ab), and thyroglobulin antibody (TG-Ab) in the GBS group were all higher than those in the CIDP and Control groups (P<0.01). The thyroid antibody positive rates in the GBS and CIDP groups were 70.10% and 14.10%, respectively (P<0.01). In the receiver operating characteristic (ROC) curve analysis, TT4, TPO-Ab, and TG-Ab were higher in the GBS group and lower in the CIDP group (P<0.01). To achieve a high specificity of 97-99%, the diagnostic cutoff value of TPO-Ab was higher than 133 IU/mL (Sensitivity: 11.34%) or lower than 0.01 IU/mL (Sensitivity: 9.09%), while the diagnostic cutoff value of TG-Ab was higher than 261.1 IU/mL (Sensitivity: 2.06%) or lower than 0.46 IU/mL (Sensitivity: 11.69%). Multivariate logistic regression analysis showed that the differences in TPO-Ab were statistically significant between GBS patients with TPO-Ab was higher than 133 IU/mL and CIDP patients (P<0.01); the differences in TG-Ab were statistically significant between GBS patients with TG-Ab was higher than 261.1 IU/mL and CIDP patients (P<0.05). Conclusion The elevation of thyroid autoantibodies was associated with GBS. TPO-Ab higher than 133 IU/mL or lower than 0.01 IU/mL and TG-Ab higher than 261.1 IU/mL or lower than 0.46 IU/mL had high specificity for differentiating between GBS and CIDP; therefore, TPO-Ab and TG-Ab can be used as biomarkers for the differential diagnosis of GBS and CIDP.